Note on the wave equation and tensor products. - Kilicman, Adem; Eltayeb, Hassan (Elsevier, 2011)
In this study we apply convolution and tensor products of distribution to solve the non-homogenous wave equation with initial condition and discuss the uniqueness and continuity of solution. We also show that the tensor product can be applied to compute the some singular integrals.